The Effectiveness of Inhaled Rosemary essential Oil in Improving Hemoglobin Concentration and Reducing Anemia Symptoms Among Pregnant Women - Reny Retnaningsih; Tut Rayani Aksohini Wijayanti; Sulistiyah Sulistiyah; Zainal Alim (Health Dynamics, 2025)
Background: Anemia during pregnancy is a global health concern that affects both maternal and fetal well-being. Iron supplementation is the primary treatment. However, its effectiveness is often hindered by poor adherence due to gastrointestinal side effects. Rosemary (Rosmarinus officinalis L.) essential oil has demonstrated antioxidant and hematopoietic potential, suggesting its utility as a complementary therapy. This study aims to evaluate the effectiveness of inhaled rosemary essential oil in improving hemoglobin concentration and reducing anemia releated symptoms among second trimester pregnant women with mild to moderate anemia. Methods: A quasi-experimental pretest-posttest control group design was utilized with 60 pregnant women who were randomly assigned to intervention (n=30) and control (n=30) groups. The intervention group inhaled rosemary essential oil for 15 minutes twice day throughout a duration of four weeks, while both groups continued iron supplementation. Hemoglobin levels were measured pre and post intervention using a hematology analyser, and anemia symptoms (fatigue, dizziness and shortness of breath) were assessed using the Visual Analog Scale (VAS). Results: The intervention group showed a significantly greater increase in hemoglobin levels compared to the control group (+1,20 g/dL vs. +0,40 g/dL; p<0,001), indicating improvement in clinical symptoms of anemia. Conclusions: Inhalation of rosemary essential oil signicantly improves hemoglobin concentration and alleviates anemia related symptoms in pregnant women. It offers a safe, natural and non-invasive complementary approach to enhance maternal health during pregnancy.